Impact of corticosteroids in hospitalised COVID-19 patients - Ho, Kam Sing (BMJ Open Respir Res, 2021)
BACKGROUND: Corticosteroids are a potential therapeutic agent for patients with COVID-19 pneumonia. The RECOVERY (Randomised Trials in COVID-19 Therapy) trial provided data on the mortality benefits of corticosteroids. The study aimed to determine the association between corticosteroid use on mortality and infection rates and to define subgroups who may benefit from corticosteroids in a real-world setting. METHODS: Clinical data were extracted that included demographic, laboratory data and details of the therapy, including the administration of corticosteroids, azithromycin, hydroxychloroquine, tocilizumab and anticoagulation. The primary outcome was in-hospital mortality. Secondary outcomes included intensive care unit (ICU) admission and invasive mechanical ventilation. Outcomes were compared in patients who did and did not receive corticosteroids using the multivariate Cox regression model. RESULTS: 4313 patients were hospitalised with COVID-19 during the study period, of whom 1270 died (29.4%). When administered within the first 7 days after admission, corticosteroids were associated with reduced mortality (OR 0.73, 95% CI 0.55 to 0.97, p=0.03) and decreased transfers to the ICU (OR 0.72, 95% CI 0.47 to 1.11, p=0.02). This mortality benefit was particularly impressive in younger patients (<65 years of age), females and those with elevated inflammatory markers, defined as C reactive protein ≥150 mg/L (p≤0.05), interleukin-6 ≥20 pg/mL (p≤0.05) or D-dimer ≥2.0 µg/L (p≤0.05). Therapy was safe with similar rates of bacteraemia and fungaemia in corticosteroid-treated and non-corticosteroid-treated patients. CONCLUSION: In patients hospitalised with COVID-19 pneumonia, corticosteroid use within the first 7 days of admission decreased mortality and ICU admissions with no associated increase in bacteraemia or fungaemia.